Gentlemen first? 'Broken stick' modelling reveals sex‐related homing decision date in migrating seabirds. (12th September 2013) - Thiebot, J.‐B.; Authier, M.; Trathan, P. N.; Bost, C.‐A.
Abstract Technical progress in animal‐borne tracking and movement data analysis has facilitated the understanding of the interplay between successive periods in the life cycle of migratory animals. We investigated how sex differences on the constraints of homing may influence migration to breeding areas in crested penguins (genus Eudyptes). We used a novel approach to infer homing decision date, a precise point in time that translates statistically as a change point in the current distance of the animal to its colony ('broken stick' modelling approach, R codes provided here). We applied this approach to geolocation tracking data on migration in three Eudyptes species, from three localities in the southern Indian Ocean (five populations). Sex had a subtle and consistent influence on the temporal activity of the 66 animals during their migratory journey. Males began migration to the breeding localities earlier than females, by an average of 9.1 (range: 4.5–13.5) days. This difference was statistically significant in 4 of 5 populations, and occurred among all species, sites and years surveyed. Our study shows an original application of a recent modelling approach to detect change point in movement data. Our results suggest that sex‐specific constraints related to breeding in migrating animals may also modify activity schedules well before breeding commences.